Educational Communication and Learning: The Foundation of Effective Interaction in the Teaching and Learning Process - Ni Putu Diana Sari; Petrus Sepi Kogoya; I Gede Satria Aditya Wibawa; Ida Bagus Putrayasa; I Wayan Rasna; I Nengah Suandi (Bulletin of Pedagogical Research, 2025)
This paper explores the pivotal role of educational communication as a foundational element in fostering effective interaction within the teaching and learning process. Adopting a literature review approach, this study synthesizes a wide range of scholarly sources related to educational communication and instructional practices. The analysis highlights the integration of interactive and dialogical communication, underscoring the importance of two-way information exchange between teachers and students in creating a more dynamic and participatory learning environment. The paper further examines critical aspects of educational communication, such as message clarity, appropriate media selection, and effective feedback management, identifying them as key indicators of successful communication in educational settings. Emphasis is placed on the need for flexible communication strategies that consider linguistic diversity and social contexts to ensure inclusive and effective learning across various classroom environments. The findings reveal that well-structured educational communication not only enhances the quality of classroom interaction but also strengthens teacher-student relationships and contributes to the optimal attainment of learning outcomes. This study contributes to the existing body of knowledge by offering a comprehensive framework for applying educational communication strategies that align with contemporary pedagogical demands, thereby informing educators, policymakers, and instructional designers in developing more inclusive and effective teaching practices.